Aplicación de instrumentos de planificación, estrategia para equilibrar el déficit de precariedad de hábitat para el barrio Porvenir Río del Municipio de Mosquera (2019)
In several areas of the national and global territory, informal settlements with a great lack of appropriate urban infrastructure have been evidenced, generating inadequate housing developments. This paper addresses the concepts of poverty and habitat insecurity focused on the urban infrastructure deficiency that have been presented at the local level, identifying the characteristics of urban precariousness in the sector.